Health Risk Behaviors and Self-Esteem Among College Students: Systematic Review of Quantitative Studies. - Arsandaux, Julie; Montagni, Ilaria; Macalli, Melissa; Bouteloup, Vincent; Tzourio, Christophe; Galéra, Cédric (International Journal of Behavioral Medicine, 2020)
Background: Due to their impact on premature mortality and long-term disabilities, a better understanding of health risk behavior (HRB) determinants among college students is crucial in order to build the most appropriate prevention tools. Although self-esteem appears to be a relevant candidate, a clear picture summarizing its multiple links with HRB is lacking to guide clinicians and researchers. This study aims to provide a systematic review of the associations between health risk behavior and self-esteem among college students. Methods: This search was performed in several databases on 02/02/17. Study eligibility criteria were original articles in peer-reviewed journals, in English; observational quantitative studies; among college students; and investigated the association between self-esteem and HRB. The PRISMA statements were complied with. Results: One hundred fifteen articles were included: 46 on substance use, 35 on sexual behavior, 11 on nutritional habits, 27 on physical activity, and 5 on other HRB. Most studies reported an association between higher self-esteem and healthier behavior. For alcohol consumption and number of sexual partners, both negative and positive associations have been reported. Directionality was investigated in a few studies suggesting potential bidirectional effects. Conclusions: This review points out the need for consensus for the definition of self-esteem and HRB. There was high heterogeneity in (1) the measurement of self-esteem either in the concept measured (global vs. domain) or in the way to implement validated tools; and (2) the definition of HRB. Self-esteem seems to be a relevant target to intervene on HRB, especially alcohol abuse and physical activity. Trial Registration: Registration number: PROSPERO (ID = CRD42017056599).